2017
DOI: 10.3390/pr5020023
|View full text |Cite
|
Sign up to set email alerts
|

Aqueous Free-Radical Polymerization of Non-Ionized and Fully Ionized Methacrylic Acid

Abstract: Water-soluble, carboxylic acid monomers are known to exhibit peculiar kinetics when polymerized in aqueous solution. Namely, their free-radical polymerization rate is affected by several parameters such as monomer concentration, ionic strength, and pH. Focusing on methacrylic acid (MAA), even though this monomer has been largely addressed, a systematic investigation of the effects of the above-mentioned parameters on its polymerization rate is missing, in particular in the fully ionized case. In this work, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 24 publications
2
10
0
Order By: Relevance
“…As described in the Introduction section, the role of counterions on the overall rate of polymerization as well as on the rate of propagation for ionized monomers has been a matter of interest for many years and remains a current challenge. ,,,, The overall understanding is that counterions increase the rate of polymerization and, as anticipated but not yet systematically studied, increase the k p values by screening the repulsive electrostatic interactions between the positively charged species involving monomers, growing radical chain ends and polymer chains. Figure a,b shows a graphical representation of k p data from Tables and to visualize the dependence of k p on monomer concentration and temperature for both TMAEMC and MAPTAC.…”
Section: Resultsmentioning
confidence: 99%
“…As described in the Introduction section, the role of counterions on the overall rate of polymerization as well as on the rate of propagation for ionized monomers has been a matter of interest for many years and remains a current challenge. ,,,, The overall understanding is that counterions increase the rate of polymerization and, as anticipated but not yet systematically studied, increase the k p values by screening the repulsive electrostatic interactions between the positively charged species involving monomers, growing radical chain ends and polymer chains. Figure a,b shows a graphical representation of k p data from Tables and to visualize the dependence of k p on monomer concentration and temperature for both TMAEMC and MAPTAC.…”
Section: Resultsmentioning
confidence: 99%
“…The group of Buback has successfully measured the additional rate coefficients associated with backbiting for both AA 8,11 and acrylamide (AM) 12 homopolymerizations. It has been demonstrated that the homopolymerization rates of fully ionized methacrylic acid (NaMA) 13 and acrylic acid (NaA) 14 are greatly reduced from those of their nonionized counterparts in aqueous solution, with the relative reduction in the rate of conversion dependent on initial monomer concentration; furthermore, the reaction rate increases in the presence of added salt such as NaCl. PLP-SEC investigations on k p of NaMA 15 and NaA 16 have highlighted the importance of counterions in the screening of monomer-radical electrostatic interactions, with an increase in k p observed with an increased concentration of counterions.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Additionally, experimental setups in unstirred batch reactors, for example, NMR tubes, have been performed. 10,11 Solutions consisting of a monomer and initiator are degassed and placed in 5 mm NMR tubes (2 mm NMR tubes for improved heat transfer). Here, the reaction progress is measured by in situ NMR.…”
Section: Introductionmentioning
confidence: 99%
“…Batch reactors and calorimeters, which are mostly reactor vessels with advanced heat flux management, can be equipped with common online or offline measurement methods. Additionally, experimental setups in unstirred batch reactors, for example, NMR tubes, have been performed. , Solutions consisting of a monomer and initiator are degassed and placed in 5 mm NMR tubes (2 mm NMR tubes for improved heat transfer). Here, the reaction progress is measured by in situ NMR.…”
Section: Introductionmentioning
confidence: 99%